MEAN AND VOLATILITY SPILLOVER ANALYSIS AS A PROXY FOR BRIC INTEGRATION - Samuel, Andrews (2014)
This dissertation examines the mean and volatility spillover effects of BRIC equity indexes and regional and global equity indexes as a proxy for integration. Spillover effects are measured using a two-step GARCH process as set out by Bhar & Nikolova (2007) using the standardised residuals of the regional and global equity indexes in the mean and variance equations of BRIC equity returns. GARCH (1, 1), GARCHM (1, 1) and EGARCH (1, 1) models are all used to examine spillover effects. The time period between September 1995 and June 2014 is examined, with two periods considered a pre-crisis period, 01/09/1995 - 21/02/2007, and a post-crisis period, 22/02/2007 – 30/06/2014. By examining these two period this dissertation examines changes in integration through spillover effects between BRIC countries, their respective regions and the world. The results find that mean spillovers have increased between BRIC countries and the world while they have decreased with regions. This indicates that the BRIC equity price creation process has shifted away from regional influences towards global influences. While the changes between the pre-crisis and post-crisis period of volatility spillovers provided mixed results